Room-temperature CO2 conversion to carbon using liquid metal alloy catalysts without external energy input - Gagrai, Mahesh Kumar (Journal of the Indian Chemical Society, 2024)
Conversion of CO2 to carbon using a catalyst typically requires significant energy input such as heat, pressure, or electricity. This is due to its strong bonds and the energy needed to initiate the reaction. The energy requirement for CO2 conversion may also lead to carbon emissions if sources are fossil-based. There is less exploration at low temperatures and without an external energy CO2 conversion to solid carbon. Here, we show a liquid metal alloy (In0.2Ga0.8) used as a catalyst for converting CO2 to carbon at room temperature without external energy. The carbon formed was characterized, and the calculated free energy of the reduction reaction was −530 kJ mol−1.The catalyst coated over a ceramic surface observed similar phenomena of CO2 conversion to carbon at room temperature. The conversion was five times higher at catalyst-coated ceramic membranes than at bulk catalysts. The CO2 conversion efficiency was 60 % at the catalytic membrane for continuous flow of CO2 at room temperature. EDX and XPS studies confirmed the formation of carbon at the catalyst surface. Our study may open the topic of membrane-based catalysis of CO2 for practical carbon conversion at lower operating costs at the industrial scale to achieve net-zero emissions. [Display omitted] •Achieved 60 % conversion efficiency of CO2 to carbon with zero external energy input.•The Gibbs free energy of the reaction was −530 kJ mol⁻1.•The In₀.₂Ga₀.₈ loaded tubular ceramic substrate tested for CO2 reduction of over 288 h at 30 °C.•XPS and EDX analyses confirmed carbon species.